Blended Concessional Finance : The Rise of Returnable Capital Contributions - Karlin, Arthur; Sierra-Escalante, Kruskaia (International Finance Corporation, Washington, DC, 2019)
In new and challenging markets, blended concessional finance - the combining of concessional funds with other types of finance, on commercial terms - is increasingly used to mobilize capital and accelerate high impact private sector investments. However, a relatively new approach for the provision of concessional capital for use by development finance institutions is emerging - the returnable capital model. With this new model, principal, interest, and other amounts are repaid to the original provider of funds (usually a government) on a regular basis. Because this can reduce the impact on donor government budgets, more government funds can become available for collaboration with the private sector. This note explores the effects of this new model on incentives, accounting, resource management, and reporting.